Bahan Ajar Fisika Berbasis I-SETS (Islamic, Science, Environment, Technology, Society) Terintegrasi Karakter (UPEJ Unnes Physics Education Journal, 2017)
Teaching material is a learning resource that can help teachers to facilitate the delivery of learning materials. The teaching materials used in some schools emphasize material descriptions rather than applications in everyday life. In the Curriculum 2013 there is a KI-1 that contains religious values ​​such as Islamic values ​​for Islamic schools. These Islamic values ​​can be included in teaching materials. I-SETS-based physics teaching materials (Islamic, Science, Environment, Technology, Society) are teaching materials that apply the principles of science in the form of technology to know the impacts that are generated for the environment and society, and related to Islamic values. Character education proclaimed by the government can also be integrated in I-SETS-based physics teaching materials. The purpose of this research is to compose the physics-based I-SETS-based physics learning materials, know the level of eligibility and readability, and character development. The method used in this research is Research and Development. The result of the research shows that the I-SETS-based physics-based teaching materials are characterized using several characteristics, the result of the feasibility test of physics-based I-SETS material which viewed from the aspect of content, presentation, and language shows that the teaching material is very suitable to be used. The results of the legibility test show that the teaching materials are easy to understand. The development of religious character, discipline, and responsibility after using the teaching materials, increases with the medium gain criteria.